The Effect of Chinese Square Dance Exercise on Cognitive Function in Older Women With Mild Cognitive Impairment: The Mediating Effect of Mood Status and Quality of Life - Chang, Jindong; Zhu, Wenbing; Zhang, Jia; Yong, Liming; Yang, Ming; Wang, Jibing; Yan, Jiagao (Frontiers in Psychiatry, 2021)
The present study aimed to assess the effects of square dance exercise on the cognitive function and quality of life in older women with mild cognitive impairment and to investigate the mediating role of a depressed mood and reduced quality of life in the relationship between square dance exercise and cognition. The study design was a single-blind whole-group controlled trial. A total of 136 eligible participants were divided according to their nursing home into either an experimental or control group. The nursing home grouping was determined by the drawing of lots. The Montreal Cognitive Assessment (MoCA), Quality of Life (SF-12) and Geriatric Depression Scale (GDS-15) were used to assess participants at baseline, week 9, and week 18, respectively. Generalized estimating equations (GEE) were used to compare the results at baseline with mid-test and post-test changes in cognitive function and quality of life. Maximum likelihood estimation (ML) and robust standard errors were used to perform the mediation model. The study results indicated that the experimental group (compared to the control group) had a significant improvement in cognitive function, quality of life, and mood state at baseline in the mid-test and post-test results. The results of this 18-week experiment showed that the exercise–cognition relationship was significantly mediated by a reduction in depressive symptoms (indirect effect: β= -0.375; 95%CI= -0.864 to -0.069) and an improvement in quality of life (indirect effect: β= -0.678; 95%CI= -1.222 to -0.290). This study revealed the effects of moderate-intensity square dance exercise on cognitive function and quality of life in older Chinese women with mild cognitive impairment and explored the potential mediating mechanisms. These findings can be used to inform the development of public health policies to promote brain health in older adults with mild cognitive impairment.